Shot‐to‐shot two‐dimensional photon intensity diagnostics within megahertz pulse‐trains at the European XFEL. (8th June 2022) - Guest, Trey W.; Bean, Richard; Bielecki, Johan; Birnsteinova, Sarlota; Geloni, Gianluca; Guetg, Marc; Kammering, Raimund; Kirkwood, Henry J.; Koch, Andreas; Paganin, David M.; van Riessen, Grant; Vagovič, Patrik; et al.
Abstract : Systematic fluctuations in the pulse–pulse intensity profile of a MHz X‐ray free‐electron laser (FEL) source have been observed that are not described by fundamental FEL theory. The sensitivity of these fluctuations to modifications of the electron‐beam orbit in the accelerator is demonstrated as a potential route to beam optimization. Abstract : Characterizing the properties of X‐ray free‐electron laser (XFEL) sources is a critical step for optimization of performance and experiment planning. The recent availability of MHz XFELs has opened up a range of new opportunities for novel experiments but also highlighted the need for systematic measurements of the source properties. Here, MHz‐enabled beam imaging diagnostics developed for the SPB/SFX instrument at the European XFEL are exploited to measure the shot‐to‐shot intensity statistics of X‐ray pulses. The ability to record pulse‐integrated two‐dimensional transverse intensity measurements at multiple planes along an XFEL beamline at MHz rates yields an improved understanding of the shot‐to‐shot photon beam intensity variations. These variations can play a critical role, for example, in determining the outcome of single‐particle imaging experiments and other experiments that are sensitive to the transverse profile of the incident beam. It is observed that shot‐to‐shot variations in the statistical properties of a recorded ensemble of radiant intensity distributions are sensitive to changes in electron beam current density. These changes typically occur during pulse‐distribution to the instrument and are currently not accounted for by the existing suite of imaging diagnostics. Modulations of the electron beam orbit in the accelerator are observed to induce a time‐dependence in the statistics of individual pulses – this is demonstrated by applying radio‐frequency trajectory tilts to electron bunch‐trains delivered to the instrument. We discuss how these modifications of the beam trajectory might be used to modify the statistical properties of the source and potential future applications.